Can Right Heart Catheterization Improve the Prediction of Positive Response to Resynchronization Therapy? - Karolina Barańska-Pawełczak; Wojciech Jacheć; Andrzej Tomasik; Bettina Ziaja; Michalina Mazurkiewicz; Tomasz Kukulski; Celina Wojciechowska (Biomedicines)
Background/Objectives: Cardiac resynchronization therapy (CRT) is one of the interventional methods of heart failure (HF) treatment, with the criteria for CRT device implantation based on the value of the left ventricular ejection fraction, New York Heart Association functional class, QRS complex duration, and electrocardiographic morphology. Pulmonary hypertension is an important factor influencing the prognosis of patients with HF, but its influence on CRT is not fully understood. Aim: The main aim of the study was to determine the prognostic value of baseline right heart catheterization-derived parameters on the response to CRT. Methods: It was a single-centre study with retrospective analysis of data of 39 non-ischemic HF patients. Clinical, biochemical, echocardiographic, electrocardiographic, and hemodynamic data were obtained before the CRT device implantation, and after 6 months of follow-up, non-invasive re-assessment was performed. Various criteria for the response to CRT were assessed along with the correlation between the baseline parameters. Results: After follow-up, a significant difference was found in the reduction in symptoms associated with HF, an increase achieved in the six-minute walk test distance, and a reduction in N-terminal pro-brain natriuretic peptide concentration as well as improvement of LV function assessed in echocardiographic examination. Among all parameters assessed, the baseline higher value of the transpulmonary gradient and pulmonary vascular resistance most often had a significant negative impact on meeting the criteria of response to CRT. Conclusions: The results of the analyses show that the initial assessment of pulmonary hemodynamics may be crucial in predicting the response to CRT in patients with non-ischemic cardiomyopathy.